Anorexia nervosa and depression in a 5‐year‐old girl: Treatment with focused family play therapy and medication. Issue 9 (5th July 2019) - Chatoor, Irene; Webb, Lauren E.; Kerzner, Benny
Abstract: Objective: The current case presentation examines the treatment and recovery of a 5‐year‐old girl diagnosed with comorbid anorexia nervosa and major depressive disorder. Researchers have shown that children as young as 3‐years‐old may be dissatisfied with their bodies and have concerns about their weight. This case presentation of a 5‐year‐old child demonstrates that the age range defining early onset of eating disorders can span into early childhood, which requires treatment tailored to the developmental level of these young children. Method: A new method "focused family play therapy" was applied. It goes beyond free play or structured play therapy, in that the therapist involves the parents in the play and not only models the situation which creates the child's fears, but also shows through dolls how to be brave and overcome the fears. Results: The current case report demonstrates how the combination of refeeding the child during family meals, participating in focused family play therapy to help the child overcome her fears of eating, and prescribing sertraline to treat her depression was an effective treatment for both the anorexia nervosa and depression. Discussion: This technique may be effective with children ranging in age from 3 to 6 years.